Novel technique of sclerotherapy for superficial lymphatic malformation - Hidehito Usui; Hidehito Usui; Masato Shinkai; Satoshi Tanaka; Rento Morishima; Kazuki Shirane; Takafumi Kondo; Kyoko Mochizuki; Norihiko Kitagawa (Frontiers in Pediatrics)
PurposeSuperficial lymphatic malformation (SLM), previously known as lymphangioma circumscriptum, is characterized by skin lesions that sometimes require interventional treatment. However, an effective treatment has yet to be established. We proposed an effective sclerotherapy procedure based on the pathophysiology of SLM.MethodsSeven patients with SLM who were treated at our hospital between April 2015 and April 2024 were retrospectively enrolled. To maximize the treatment effects, sclerotherapy with bleomycin targeting the SLM and LM deep beneath the SLM was performed.ResultsOf the seven patients, four were females, and three were males. The SLM sites were mucosal lesions in four cases and skin lesions in three cases. The median age at the first sclerotherapy was 10 (1–18) years. A median of one course (1–3) of sclerotherapy resulted in a marked reduction of SLM lesions on gross evaluation to the satisfaction of the patient. The median observation period was 451 (59–2,901) days. No serious complications occurred, except for transient vomiting in one patient and temporary skin pigmentation in two patients. No patient experienced recurrence requiring retreatment.ConclusionOur study suggests that sclerotherapy for the SLM and LM deep beneath the SLM may be an effective treatment for SLM.